Quality Of Work Life And Turnover Intention - The Mediating Effects Of Career And Organizational Commitment - Tarmizi, Azlin Natasha (2008)
The purpose of this study is to examine the effects of Quality of Work Life factors in explaining the turnover intention of accounting professionals in Malaysia being mediated by career and organizational commitment. A total of 121 questionnaire representing 81 % of response rate were used for statistical analysis and the result indicated that normative commitment mediates the relationship of Quality of Work Life and Turnover Intention.